Kualitas Pelayanan Kesehatan Jiwa pada Penderita Depresi di Pusat Kesehatan Masyarakat (Puskesmas) Sangurara Kelurahan Duyu Kota Palu - Riyatno Riyatno; La Samudia Dalili; Priyatna Prasetyawati; Galip Lahada (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the Quality of Mental Health Services for Depression Patients at the Sangurara Health Center, Duyu Village, Palu City. The type of research is Descriptive with a qualitative approach. The technique of determining informants is done purposively; Data collection through observation, interviews, and documentation; Data analysis used is an interactive model including data condensation, data presentation, and drawing conclusions. The results of the study show that the quality of mental health services for depression patients is optimal. Based on the Reliability dimension, that the services provided by health workers are timely; Assurance, that the service procedure is in accordance with the Standard Operating Procedure (SOP); Physical evidence, in the form of examination rooms and medical equipment is sufficient and the available room meets the minimum requirements; Empathy, that continuity of service is not carried out by health workers; and the Responsiveness dimension, that depression patients have been served quickly by health workers. It is expected that health workers will pay attention to and carry out continuity of service, namely by conducting supporting examinations to determine the development of the physical condition of depression patients.